The Chu silk manuscripts from Zidanku, Changsha (Hunan Province). - Li, Ling, 1948- (The Chinese University of Hong Kong Press, 2020)
The Silk Manuscripts from Zidanku, Changsha (Hunan) are the only pre-imperial Chinese manuscripts on silk found to date. Dating to the turn from the fourth to the third centuries BC (Late Warring States period), they contain several short texts concerning basic cosmological concepts in a diagrammatic arrangement and surrounded by pictorial illustrations. As such, they constitute a unique source of information complementing and going beyond what is known from transmitted texts. This is the first in a two-volume monograph on the Zidanku manuscripts, reflecting almost four decades of research by Professor Li Ling of Peking University. While the philological study and translation of the manuscript texts is the subject of Volume II, this first volume presents the archaeological context and history of transmission of the physical manuscripts. It records how they were taken from their original place of interment in the 1940s and taken to the United States in 1946; documents the early stages in the research on the finds from the Zidanku tomb and its reexcavation in the 1970s; and accounts for where the manuscripts were kept before becoming the property, respectively, of the Arthur M. Sackler Foundation, New York (Manuscript 1), and the Freer and Sackler Galleries, Smithsonian Institution (Manuscripts 2 and 3). Superseding previous efforts, this is the definitive account that will set the record straight and establish a new basis for future research on these uniquely important artifacts.